Porous and Dendritic Structure of Screen-Printed Electrode for in-situ Electrochemical Surface-Enhanced Raman Scattering. (22nd January 2016) - Teng, Yuanjie; Liu, Wenhan; Lan, Minbo; Ma, Suzhen; Ma, Chunan
ABSTRACT: A new surface-enhanced Raman scattering (SERS) screen-printed electrode was prepared by simultaneously reducing Ag + and H + at a high potential. The Na2 S2 O3, which has a large cumulative formation constant with Ag +, was introduced to remove the background Raman interference of Ag2 SO4 from the electrolyte. Scanning electron micrographs showed that the SERS electrode presented porous and dendritic nanostructures using 0.01 M Ag2 SO4 and 0.6 M H2 SO4, a current density of 0.425 A/cm 2, and a deposition time of 30 s. The porous (roughness factor of 78.66) and dendritic structure contributed to the SERS enhancement factor of 3.36 × 10 4 . The electrochemistry of pyridine was characterized on the SERS electrode and in-situ detection was demonstrated.